COMPARATIVE ANALYSIS OF PHYSICAL DEVELOPMENT OF PRESCHOOL CHILDREN IN THE REPUBLIC OF KARAKALPAKSTAN - Sayidaxror T. Turgunov; Javlon A. Kamilov (Central Asian Journal of Medicine, 2024)
The study assessed the physical development of 2,573 preschool children (height, limb length, foot) from urban and rural areas of Karakalpakstan. Children aged 3–5 years from the city have higher growth rates, which is associated with a favorable urban environment. At 5.5–6 years, rural children demonstrate compensatory growth acceleration. Territorial differences varied by age and gender, emphasizing the importance of environmental factors in monitoring and prevention.